An empirical analysis of business cycles in a New Keynesian model with inventories - Marcel Förster (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
This paper introduces inventories in an otherwise standard dynamic stochastic general equilibrium model. Firms accumulate inventories to facilitate sales, but face a cost of doing so in terms of costly storage of intermediate goods. Based on U.S. data we estimate the parameters of our model using Bayesian methods. The results show that accounting for inventory dynamics has a significant impact on parameter estimates and the following analyses. We find that inventories enter the New Keynesian Phillips curve as an additional and significant driving variable and make the inflation process less backward-looking. Moreover, impulse responses can change in terms of magnitude and persistence. The variance decomposition reveals substantial changes regarding the driving forces of inflation and the nominal interest rate when we consider inventory holding.
Keywords: C13; E20; E30; 330; Inventories; Bayesian Estimation; DSGE Model; Business Cycles